Integration of EduCanva in Google Sites to Improve Student Collaboration Skills in the Context of Agroindustry - Elviana Nur Salsabilla; Slamet Haryadi; Suratno; Kamalia Fitri; Hikmah Buroidah; Bea Hana Siswati; Muhamad Khoirul Anwar; Bevo Wahono; Nana Mardiana (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
This study aims to develop Google Sites-based digital learning media integrated with EduCanva to improve students' collaboration skills in agro industrial schools. The research method uses a research and development design with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through validation sheets, questionnaires, tests, interviews, and observations, then analyzed based on validity, practicality, and effectiveness. Expert validation results showed a percentage of 97.22% from subject matter experts, 84.375% from media experts, and 84.375% from learning experts in the highly valid category. The practicality test obtained a 100% response from teachers and a 92.29% response from students, both of which were categorized as very practical. The effectiveness test showed an increase in learning outcomes with an N-gain value of 0.53 (moderate category) and an increase in student collaboration skills of 11.38% from cycle I to cycle II, which was categorized as fair to good. These findings prove that Google Sites-based learning media integrated with EduCanva is feasible, practical, and effective for use in learning. The novelty of this research lies in the combination of two digital platforms that are rarely studied in the context of biology learning in agro industrial areas. This media not only improves conceptual understanding but also strengthens collaboration skills as an important 21st-century competency.